Penggunaan Lembar Kerja KWL pada Pembelajaran Tematik Terpadu Untuk Meningkatkan Kemampuan Membaca Pemahaman Teks Informasi Siswa Kelas 5 SD di Kabupaten Bandung Indonesia - Ryan Dwi Puspita; Rully Agung Yudiantara (Pusat Penerbitan Universitas (P2U) Unisba, 2017)
Abstract This study discusses KWL (Know, Want to know, Learned) worksheets applied in an integrated thematic learning to improve informational text reading comprehension (ITRC) of 5th grade elementary school. The purpose of this study was to examine the effect of the use of KWL worksheets in boosting ITRC of 5th grade when dealing with infomational text. This study applied quasi-eksperiment method. To answer the research question, this study collected data through observation, interviews, parent questionnaires, pre-test and post-test. Sample of 86 students from two elementary schools involved in this study. Findings indicated that there was significant influence on the use of KWL worksheets on ITRC of 5th grade. Statistical result showed that t test of gain of ITRC ability between experiment class and control class at level of significance 0,05 obtained sig = 0,000. The increased performance of experiment classes were supported by many factors namely: teacher intervention, students’ prior knowledge which was related to the topic, students’ process of understanding the text, availability of supporting books related to the topic and the degree of difficulty of the informational text. Keywords: Elementary School, Informational text, Know, want to know, Learned (KWL) worksheet, Reading comprehension, 5th Grade Abstrak Penelitian ini membahas tentang lembar kerja KWL pada pembelajaran tematik terpadu untuk meningkatkan kemampuan membaca pemahaman teks informasi. Tujuan penelitian ini untuk menguji pengaruh penggunaan lembar kerja KWL pada pembelajaran tematik terpadu untuk meningkatkan kemampuan membaca pemahaman teks informasi siswa kelas 5 sekolah dasar. Penelitian ini menggunakan metode eksperimen kuasi. Data dikumpulkan melalui observasi, wawancara, angket orang tua, pra tes dan pasca tes. Penelitian ini menggunakan sampel 86 siswa kelas 5 di dua sekolah dasar. Penelitian ini menunjukkan adanya pengaruh yang signifikan penggunaan lembar kerja KWL pada pembelajaran tematik terpadu untuk meningkatkan kemampuan membaca pemahaman teks informasi siswa kelas 5 sekolah dasar. Terbukti dengan hasil uji t gain kemampuan membaca pemahaman kelas eksperimen dan kelas kontrol pada taraf signifikasi 0,05 diperoleh sig=0,000. Peningkatan yang dihasilkan variatif karena faktor intervensi guru dalam membangun pemahaman siswa terhadap teks, pengetahuan awal siswa terkait dengan tema, ketersediaan buku-buku penunjang terkait dengan tema, dan tingkat kesukaran teks informasi. Kata Kunci: Lembar kerja KWL, membaca pemahaman, siswa kelas 5 sekolah dasar, teks informasi.